Freshwater Cyanobacteria of North-Eastern Australia: 3. Nostocales - Mcgregor, Glenn B. (Phytotaxa, 2018)
This is the first detailed account of the Nostocales of north-eastern Australia, and the third and final volume in the series documenting the freshwater cyanobacterial flora of this region. This monophyletic group comprises filamentous cyanobacteria which produce heterocytes and akinetes. Amongst the cyanobacteria, this group is perhaps the most morphologically diverse, occurring as single filaments, unstructured aggregations, or colonies of various arrangements, which may exhibit false-, true-, or no-branching. This volume provides keys, morphological and ecological data, and photomicrographs for 35 genera, and 93 species from nine families to enable the identification of natural populations based on stable and recognizable characters observable by light microscopy. Distributional data are based on extensive surveys incompassing 358 sites which represent the major freshwater habitats of the region including rivers and streams, palustrine and lacustrine wetlands, thermal springs, and artificial reservoirs, as well as a review of the Australian phycological literature.